The effect of resistance band training on the increase in arm muscle power of basketball extracurricular participants at SMAN 5 Malang for the 2024/2025 academic year - Ghulam, Adilahmad; Yunus, Mahmud (Journal of Strength and Conditioning, 2024)
this study aim to effect of resistance band training on increasing in arm muscle power in the basketbaal extracurricular participants for the 2024/2025 academic year. The method used in experimental approach with a one group retest and post test design. The sample conssist of all 25 participants in the basketball extracurricular. Arm muscle power is measured  using a two hand medicine ball test before and after intervention, with data analysis conducted using the T-test and SPSS Software. The results show and average increase in arm miscle power of 3.48 to 4.57, an increase of 1.09 points or 31%. T- test show significant result (p= 0,000) indicating of significant difference im the mean arm muscle power before and and after the resistance band intervention. The conclusions indicated that resistance band exercise have a notable effect on enhacing effect arm muscle strength in the basketball extracurricular. Resistance band has been proven to effectively enhance arm muscle explosiveness, which effect shooting and passing perform in basketball. The research contributes to the development arm muscle strenght for basketball extracurricular participants supporting, optimal perform in both practice and competition.